2022
DOI: 10.21037/tp-22-410
|View full text |Cite
|
Sign up to set email alerts
|

Enriched environment alleviates adolescent visceral pain, anxiety- and depression-like behaviors induced by neonatal maternal separation

Abstract: Background Neonatal maternal separation (NMS), a major kind of early life stress, increases the risk of visceral pain, anxiety- and depression-like behaviors in adulthood. An enriched environment (EE) has been shown to successfully rescue the brain from various early life psychological stressors. Therefore, this study aimed to investigate whether NMS induces visceral pain, anxiety- and depression-like behaviors in adolescents and to evaluate the impact of EE in infancy on these symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Our study showed that EE intervention during prepuberty and puberty effectively prevented/alleviated NMS-induced visceral pain, anxiety, and depressive behaviors and reversed the increase in plasma corticosterone, yet EE intervention in early adulthood had no significant effect. Clinical and basic studies have shown that early life stress may negatively affect brain development, neuroplasticity, and behavior, and increase individual vulnerability to chronic pain and psychiatric disorders, including chronic visceral pain, depression, and anxiety (2,(5)(6)(7)16). In this study, we observed that exposure to NMS resulted in a decreased pain threshold and disturbed emotional response in mice.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Our study showed that EE intervention during prepuberty and puberty effectively prevented/alleviated NMS-induced visceral pain, anxiety, and depressive behaviors and reversed the increase in plasma corticosterone, yet EE intervention in early adulthood had no significant effect. Clinical and basic studies have shown that early life stress may negatively affect brain development, neuroplasticity, and behavior, and increase individual vulnerability to chronic pain and psychiatric disorders, including chronic visceral pain, depression, and anxiety (2,(5)(6)(7)16). In this study, we observed that exposure to NMS resulted in a decreased pain threshold and disturbed emotional response in mice.…”
Section: Discussionmentioning
confidence: 55%
“…In contrast to the negative effects of early life stress, EE had a positive effect on brain development and behavior. We have previously shown that EE from P1 to P40 can alleviate visceral pain and mental disorders in adolescence (7). Since EE appears to ameliorate stress-induced negative responses in early life, is there an optimal time window for intervention?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Noxious stress is known to cause dysfunction of the HPA axis, which is associated with visceral pain and psychiatric symptoms. In contrast, an EE improves chronic pain and psychiatric disorders caused by early life stress, including visceral pain, anxiety, and depression (8). Several studies have shown that an EE can reduce anxiety-and depressive-like behaviors in animals (9,10).…”
Section: Original Articlementioning
confidence: 99%